1-(4-Hydroxyphenyl)-2H-tetrazole-5-thione as a leveler for acid copper electroplating of microvia. Issue 25 (31st May 2022) - Teng, Xulingjie; Tao, Zhihua; Long, Zhiyuan; Liu, Guanting; Tao, Xuefei
Abstract : Microvia filling by copper electroplating was performed using plating solution with 1-(4-hydroxyphenyl)-2 H -tetrazole-5-thione (HPTT) as the leveler. Abstract : Microvia filling by copper electroplating was performed using plating solution with 1-(4-hydroxyphenyl)-2 H -tetrazole-5-thione (HPTT) as the leveler. Galvanostatic Measurements (GMs), Linear Sweep Voltammetry (LSV) and Electrochemical Impedance Spectroscopy (EIS) tests were carried out to investigate the electrochemical behaviors of HPTT and its synergistic effect with other additives, in comparison with 1-phenyltetrazole-5-thione (PMT). GMs showed a convection-dependent interaction between PEP and HPTT. LSV and EIS tests indicated both HPTT and PMT enhanced the inhibition effect of PEP, and the synergistic effect of HPTT and PEP was stronger than that of PMT. Cross-section images illustrated the filling rate of the microvia with a 150 μm diameter and a 75 μm depth was 95.6% in 60 minutes with HPTT as the leveler. Frontier Molecular Orbitals (FMO) and Electrostatic Potential (ESP) of HPTT and PMT using quantum chemical calculations predicted the reaction sites for electrophilic and nucleophilic attack. Quantum chemical calculations suggested that HPTT is easier than PMT to bond to a copper surface and PEP.